흙 놀이를 통한 유아자폐증치료과정 연구 - 김성민(Sung-Min Kim) (한국콘텐츠학회 논문지, 9(3), 2009)
The structure of modern society are complex, fast, overflowing of individualism and losing of independence through the standardization of human relationship. The frequency increased that children watch television and play computer game alone through this structure. Also, the mental disorder like as autism tend to be increase for childhood because, parents overprotect, unmethodical bringing up children, emotional disturbance and effect of genetic. Therefore, research and case study of art therapy publish that illustrates a tendency of developing and growing. On the base of this situation art therapy realize more important than before and gain power. Therefore, this research consider that clay therapy effect for autistic just children and investigate function of catharsis through the case study. Also, make study that social rappot and function of catharsis develop for children who has autism. The suggest effect of synergy which come from clay therapy(education of ceramic) and development of education program. 복잡하고 빠르게 돌아가는 현대사회의 사회적 대상관계의 특징은 개인주의 팽배와 획일적 인간 관계속의 주체성 상실 등을 들 수 있다. 이러한 구조상의 무관심속에 아동들은 혼자서 텔레비전을 보거나 컴퓨터에 빠져 지내는 경우가 늘어나고 있다. 또한 어머니들의 과보호, 불규칙적인 양육태도, 정서적 외상 및 유전적 영향으로 인해 아동기 정신 발달 장애 빈도가 높아지고 있는 추세이다. 이러한 추세에 발맞추어서 미술치료에 대한 연구와 사례들이 많이 발표되고 있으며 미술치료의 중요성이 대두되고 있다. 이에 본 연구에서는 가장 인간과 밀접한 관계가 있는 자연 매체인 점토를 통한 치료가 발달 장애(자폐아)를 가지고 있는 아동에게 미치는 영향과 효과에 대하여 고찰해보고 또한 점토치료가 이러한 장애를 가진 아동들의 사회적 대상관계와 정화작용의 발전에 미치는 영향에 대해 제시하며 이를 바탕으로 생기는 시너지 (Synergy Effect) 효과와 이러한 효과를 극대화 시킬 수 있는 교육 프로그램 개발 연구에 대해서 제시하려한다.